In vitro and in vivo characterization of the bifunctional μ and δ opioid receptor ligand UFP‐505. (14th May 2018) - Dietis, N; Niwa, H; Tose, R; McDonald, J; Ruggieri, V; Filaferro, M; Vitale, G; Micheli, L; Ghelardini, C; Salvadori, S; Calo, G; Guerrini, R; et al.
Abstract : Background and Purpose: Targeting more than one opioid receptor type simultaneously may have analgesic advantages in reducing side‐effects. We have evaluated the mixed μ opioid receptor agonist/ δ opioid receptor antagonist UFP‐505 in vitro and in vivo . Experimental Approach: We measured receptor density and function in single μ, δ and μ /δ receptor double expression systems. GTPγ 35 S binding, cAMP formation and arrestin recruitment were measured. Antinociceptive activity was measured in vivo using tail withdrawal and paw pressure tests following acute and chronic treatment. In some experiments, we collected tissues to measure receptor densities. Key Results: UFP‐505 bound to μ receptors with full agonist activity and to δ receptors as a low efficacy partial agonist At μ, but not δ receptors, UFP‐505 binding recruited arrestin. Unlike morphine, UFP‐505 treatment internalized μ receptors and there was some evidence for internalization of δ receptors. Similar data were obtained in a μ /δ receptor double expression system. In rats, acute UFP‐505 or morphine, injected intrathecally, was antinociceptive. In tissues harvested from these experiments, μ and δ receptor density was decreased after UFP‐505 but not morphine treatment, in agreement with in vitro data. Both morphine and UFP‐505 induced significant tolerance. Conclusions and Implications: In this study, UFP‐505 behaved as a full agonist at μ receptors with variable activity at δ receptors. This bifunctional compound was antinociceptive in rats after intrathecal administration. In this model, dual targeting provided no advantages in terms of tolerance liability. Linked Articles: This article is part of a themed section on Emerging Areas of Opioid Pharmacology. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.14/issuetoc